2012
DOI: 10.1111/1471-0528.12081
|View full text |Cite
|
Sign up to set email alerts
|

Graft‐related complications and biaxial tensiometry following experimental vaginal implantation of flat mesh of variable dimensions

Abstract: Population Twenty adult parous Texel ewes.Methods Sheep were implanted with Gynemesh M, a 28-g/m² polypropylene mesh reinforced with polyglecaprone fibres, under general anaesthesia. Dissection into the rectovaginal septum was performed to accommodate a flat 50 9 50 mm (n = 10) or 35 9 35 mm (n = 10) mesh, which was sutured to the underlying tissues. A 50 9 50 mm mesh was laid over a primarily sutured, fullthickness, 40-mm longitudinal abdominal wall incision. Sacrifice was at 60 days (n = 10) or 90 days (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 26 publications
3
53
0
Order By: Relevance
“…Sheep have been frequently used in vaginal surgery training that is, vaginal hysterectomy or transvaginal meshes insertion [56,57]. The second approach was used also in reproductive medicine research to test novel implant materials that is, collagen coated or electrospun meshes [13,15,58,59]. Other methodologic strengths are that we used ball-burst testing which more closely represents the in vivo-biomechanical situation as compared to uniaxial testing, often used in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sheep have been frequently used in vaginal surgery training that is, vaginal hysterectomy or transvaginal meshes insertion [56,57]. The second approach was used also in reproductive medicine research to test novel implant materials that is, collagen coated or electrospun meshes [13,15,58,59]. Other methodologic strengths are that we used ball-burst testing which more closely represents the in vivo-biomechanical situation as compared to uniaxial testing, often used in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Sheep may be alternatives as their pelvic floor anatomy and dimensions as well as the microscopic architecture have many similarities to that of humans [11,12]. We and others have recently become interested in sheep for pelvic floor research and experimental surgery [13][14][15]. For that purpose, we previously compared the pelvic floor anatomy and tissue composition of reproductive, pregnant, and postpartum ewes to that of women [11,12,[16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, in a rabbit model, histological and biomechanical differences between abdominal and vaginal implantations were noted [31]. On the other hand, no biomechanical differences were noted when a synthetic material was implanted on the abdomen and in the vagina of a sheep model [32]. However, this is uncertain in the rat owing to the limitation of the vaginal route in this model.…”
Section: Discussionmentioning
confidence: 94%
“…Recent animal studies in sheep confirmed a site specific response to implanted PPL mesh, where a 5 × 5 cm piece of PPL mesh led to contraction and erosion in 3 out of 10 sheep in 12 months when implanted vaginally in contrast to no erosions in abdominal implantations [49]. The animal studies also showed that the host response to the PPL initiated by macrophages in the mesh-tissue interface was mainly an M1 (proinflammatory) response, instead of an M2 (remodeling) response, characterized by secretion of matrix metalloproteinases and pro-inflammatory cytokines leading to a vigorous foreign body reaction [50].…”
Section: The Failure Of Ppl In the Pelvic Floormentioning
confidence: 94%